KEWENANGAN PERADILAN AGAMA DALAM PENYELESAIAN SENGKETA EKONOMI SYARI’AH - Oktavi Maulizar (AL-ILMU, 2022)
The more developed the syari'ah economy and other business activities it is possible that the number of disputes that occur will continue to increase. Business disputes are commonplace, however, there have been various attempts to resolve these disputes. In this case, disputes in shari'ah economic disputes can be carried out in two ways, namely litigation and non-litigation. The birth of Law Number 3 of 2006 concerning Amendments to Law Number 7 of 1989 concerning the Religious Courts in conjunction with Law Number 50 of 2009 concerning Amendments to Law Number 7 of 1989 concerning the Religious Courts which contains the expansion of the authority of the Religious Courts in resolving economic disputes sharia. However, in practice in the field, there is a dualism of law regarding which institution has the right to adjudicate sharia economic disputes. The results of this study found that based on the Supreme Court Circular No. 8 of 2008 confirms the existence of religious courts in executing decisions of the National Syari'ah Arbitration Board as well as handling and deciding cases of sharia economics. So that the competence of the Religious Courts to decide syari'ah economic cases becomes absolute competence because it is supported by the legal basis of Law Number 3 of 2006 concerning Religious Courts Article 49 Paragraph (2), Law Number 21 of 2008 concerning Islamic Banking Article 55 , and Supreme Court Circular Number 8 of 2008 concerning the Execution of the Decision of the National Syari'ah Arbitration Board.Keywords: Dispute Resolution, Shari’ah Economic, Authority of Religious Courts.